2019
DOI: 10.4103/eus.eus_52_19
|View full text |Cite
|
Sign up to set email alerts
|

Drainage of the right liver using EUS guidance

Abstract: Hepaticogastrostomy (HGS) has been reported for the management of palliative malignant hilar stricture and involves draining the left liver as rescue therapy. For the management of this complex stenosis, another new option for draining the right liver under EUS guidance was introduced. Ten publications involving 38 patients have been reported in the literature, in which the following two main techniques have been described: direct puncture of the right liver from the bulbus and the bridge technique allowing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The proportion of patients with duodenal/papillary invasion and surgically altered anatomy ranged from 0% to 91% [20,24] and 0% [20,25,26,27] to 70% [28], respectively. The rate of patients with hilar stenosis was highly variable (0% [27,29,30,31,32,33,34] to 100% [20,25,26,35,36]). The transgastric approach was used exclusively in 24 studies, whereas the use of this approach ranged from 80% [21] to 97% [37] in the other studies; one study used only the transduodenal approach [38].…”
Section: Characteristics Of Included Patientsmentioning
confidence: 99%
“…The proportion of patients with duodenal/papillary invasion and surgically altered anatomy ranged from 0% to 91% [20,24] and 0% [20,25,26,27] to 70% [28], respectively. The rate of patients with hilar stenosis was highly variable (0% [27,29,30,31,32,33,34] to 100% [20,25,26,35,36]). The transgastric approach was used exclusively in 24 studies, whereas the use of this approach ranged from 80% [21] to 97% [37] in the other studies; one study used only the transduodenal approach [38].…”
Section: Characteristics Of Included Patientsmentioning
confidence: 99%
“…Ogura et al [ 75 ] reported success using a novel “bridge” technique which involves placement of a stent across the HBO, thus connecting the right and left intrahepatic, followed by EUS-HGS[ 75 ]. Both techniques are challenging and only a small number of cases performed in referral centers have been reported to date[ 76 ]. In addition, EUS-HGS may be contraindicated in patients with large abdominal ascites (preventing fistula formation with increased risk of stent migration) and unresectable gastric cancer.…”
Section: Eus-guided Hepaticogastrostomymentioning
confidence: 99%
“…For EUS-BD of the right-side of the liver, two main techniques have been described: direct puncture of the rightside of the liver from the bulbus (EUS-HDS), as first reported by Park et al in 2013 [3], and a bridge technique that allows drainage of the right-side of the liver from the left via hepaticogastrostomy (the bridge technique) [4]. In this case, the latter technique could not be applied because of the left-sided liver metastasis; the former was feasible, but only 13 further cases of the technique have been reported [5]. In cases such as this, where we were unable to obtain a cholangiogram using a contrast agent, EUS-BD might be preferable because of its rapidity and cost-effectiveness.…”
mentioning
confidence: 94%